NILAI BUDAYA DALAM CERITA RAKYAT HIKAYAT DATUK TUAN BUDIAN DAN SULTAN DOMAS PEMIMPIN YANG SAKTI DAN BAIK HATI - Erwin Wibowo (Balai Bahasa Kalimantan Barat, 2019)
This study aims to describe the cultural values contained in the folklore of Hikayat Datuk Tuan Budian, and Sultan Domas Pemimpin yang Sakti dan Baik hati. The method used in this research is descriptive and data in forms of words which are quotations. The source of folklore is a book entitled Hikayat Datuk Tuan Budian, and Sultan Domas Pemimpin yang Sakti dan Baik hati published by Kantor Bahasa Lampung in 2017. Results of this study is there are cultural values in the two books of folklore. Cultural values which can include faith, pray to God, diligent prayer, thanking God and believe in fortune all came from God cooperate, respect, responsible, altruism general, helper and affection, helping each other, living in harmony, exemplary, helpless, generous, and in love of peace, patience, gratitude, independence, hard worker, exemplary, wise, love of the environment, courage, vigilance, belief in religious teachings, and utilizing nature as well as possible.